Feeding styles of caregivers of children 6-23 months of age in Derashe special district, Southern Ethiopia - Wondafrash Mekitie; Amsalu Tseganeh; Woldie Mirkuzie (BMC, 2012)
Abstract Background Apart from basic determinants, appropriate child care practices are important in prevention of growth faltering and undernutrition. Providing safe and appropriate quality complementary foods is crucial to child growth and development. However, some children in low-income communities grow normally mainly due to proper caregiver feeding behaviors. Hence, the objective of this study was to determine caregivers' feeding styles as well as to indentify predictors in Derashe special district, Southern Ethiopia. Methods A community based cross-sectional study design was employed in the seven randomly selected Kebeles (smallest administrative unit) of Derashe special district. A total of 826 caregivers provided data pertaining to socio-demographic variables. However, 764 caregivers had complete data for the outcome variable (caregiver feeding style). A multistage stratified sampling technique was used to identify study subjects. An adapted Caregiver's Feeding Styles Questionnaire (CFSQ) was used to gather information about caregivers' feeding styles. Multivariate multinomial logistic regression was employed to identify predictors of caregivers' feeding style. Results The majority (80.6%) of caregivers were biological mothers. Nearly seventy-six percent of the caregivers practiced a responsive feeding style. Caregivers other than the biological mother favoured a laissez-faire feeding style, while caregivers residing in rural Kebeles were more responsive. Caregivers with a breastfeeding frequency of more than eight times predicted both laissez-faire (RRR = 1.88; 95% CI = 1.03-3.41) and controlling (RRR = 1.7; 95% CI = 1.02-2.85) feeding styles as compared to responsive feeding. Conclusion Responsive feeding was the commonest style practiced by the caregivers. Many of the caregivers who were rural residents and birth parents have been responsive in child feeding. The instruments needed to be validated in the Ethiopian context and an additional prospective study based on direct observation of caregiver-child interactions is recommended.